Note—On Marketing Strategy and the Optimal Production Schedule—A Rejoinder - Leitch, Robert Alan (Management Science, 1976)
Author's rejoinder to the discussion about his paper (Leitch, R. A. 1974. Marketing strategy and the optimal production schedule. Management Sci. 21 (3) 302–312.).